2015
DOI: 10.2807/1560-7917.es2015.20.6.21032
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of infant pertussis in Sweden 1998–2012; severity of disease in relation to the national vaccination programme

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 16 publications
(17 reference statements)
6
29
1
1
Order By: Relevance
“…Although the existence of herd protection induced by acellular pertussis vaccines has been challenged, population-based epidemiological surveillance for pertussis in Sweden following introduction of the acellular vaccine demonstrated herd protection among infants too young to receive a vaccine and older infants unvaccinated against pertussis (430). In addition, epidemiological modeling based on a model originally conceived by Rohani et al suggests that achieving the observed reductions in pertussis would be impossible in the absence of herd protection (431,432).…”
Section: Vaccine-induced Immunitymentioning
confidence: 99%
“…Although the existence of herd protection induced by acellular pertussis vaccines has been challenged, population-based epidemiological surveillance for pertussis in Sweden following introduction of the acellular vaccine demonstrated herd protection among infants too young to receive a vaccine and older infants unvaccinated against pertussis (430). In addition, epidemiological modeling based on a model originally conceived by Rohani et al suggests that achieving the observed reductions in pertussis would be impossible in the absence of herd protection (431,432).…”
Section: Vaccine-induced Immunitymentioning
confidence: 99%
“…Although there is some epidemiological evidence of herd immunity following aP vaccine administration [42,43], recent mathematical modeling studies from Australia, England and Wales and the USA [5], as well as data from a non-human primate (baboon) model of pertussis that closely resembles the human disease [44], support the hypothesis that transition from wP to aP vaccines may be associated with disease resurgence. In baboons, aP vaccines protect against disease but fail to prevent colonization and transmission, confirming recent mice data [44,45].…”
Section: Transmission and Herd Immunitymentioning
confidence: 93%
“…Recent reports have attempted to determine risk factors and predictors of fatal outcome in infants suffering from critical pertussis. A study of pertussis in Swedish infants highlighted the high rate (70%) of hospitalization of pertussis cases among young infants ( < 3 months old) and the protective effects of vaccination against fatal disease, since all nine deaths occurred in unvaccinated infants [67 ▪ ]. In a smaller study of 17 cases of critical pertussis in Tunisia, there was a high rate of fatal outcome (23%) and significant predictors of mortality included leukocytosis, as well as tachycardia, seizures, and shock [68].…”
Section: Critical and Fatal Pertussis In Infantsmentioning
confidence: 99%
“…However, recent reports have highlighted the benefit of early antibiotic treatment for young infants with critical pertussis. In the Swedish study, starting antibiotic treatment within the first 6 days after cough onset was associated with shorter duration of coughing than those initiating treatment 2 weeks after cough onset [67 ▪ ]. Similarly, in an Australian study of household attack rates, there was an increased risk of transmission from the primary case to contacts when antibiotic treatment was initiated later than 7 days after the onset of symptoms [73 ▪ ].…”
Section: Novel Potential Treatments For Pertussismentioning
confidence: 99%